Pentingnya Manajemen Keuangan dalam Lembaga Pendidikan - Siswadi, Siswadi; Nanik Rodiyah (Al-Maqashid: Journal of Economics and Islamic Business, 2024)
Schools become producers of individuals who are intellectually capable and skilled. School is a formal educational environment, as well as forming students' personalities whose aim is to achieve 3 factors, namely cognitive, affective and psychomotor aspects. This research aims to answer, describe and analyze the research problem formulation which consists of: How is Financial Management in Educational Institutions?, (2) What are the Principles of Financial Management in Educational Institutions?. The research method used in this research is a qualitative research method. Qualitative research is a type of research whose findings are not obtained through statistical procedures or other forms of calculation. Qualitative research methods are used to obtain in-depth data, data that contains meaning. Therefore, qualitative research does not emphasize generalization. The type of research used is field research, namely research going into the field to make observations about a phenomenon in a natural state. The results of this research concluded that: (1) The aim of financial management in educational institutions is to maximize company value, (2) the function of financial management in educational institutions is the main activity that must be carried out by those responsible in certain fields. (3) Financial Management plays a big role in running a company or educational institution because a good financial system will produce good products too.